2021
DOI: 10.1016/j.sjbs.2021.06.024
|View full text |Cite|
|
Sign up to set email alerts
|

Target and non-target effects of Foeniculum vulgare and Matricaria chamomilla combined extract on Culex pipiens mosquitoes

Abstract: The present study focused on extracting green larvicides from extracts of the combination of Foeniculum vulgare and Matricaria chamomilla using different solvents of increasing polarity in a Soxhlet extractor and evaluating their ovicidal, larvicidal, and cytotoxic activities. The most promising among all tested extracts was hexane extract. The ovicidal activity of the hexane PH2 extract resulted in a significant (p < 0.05) decrease in egg hatchability from 95.00 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The histological investigation showed changes in the midgut region of Cx pipiens due to the toxic effect of the hexane extract of G. mangostana. Similar effect has been shown also with Foeniculum vulgare and Matricaria chamomilla hexane extract (Al-Mekhlafi et al, 2021). The toxicity effect of Epaltes divaricate hexane extract on the midgut caused severe damage to gut tissues such as the peritrophic matrix, the epithelial layer, and the brush border (Amala et al, 2021).…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 68%
See 1 more Smart Citation
“…The histological investigation showed changes in the midgut region of Cx pipiens due to the toxic effect of the hexane extract of G. mangostana. Similar effect has been shown also with Foeniculum vulgare and Matricaria chamomilla hexane extract (Al-Mekhlafi et al, 2021). The toxicity effect of Epaltes divaricate hexane extract on the midgut caused severe damage to gut tissues such as the peritrophic matrix, the epithelial layer, and the brush border (Amala et al, 2021).…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 68%
“…After 24 h, the dead larvae were counted. Larvae were considered dead if they could not reach the surface or move when touched with a wooden stick (Al-Mekhlafi et al, 2021).…”
Section: Larvicidal Activitymentioning
confidence: 99%
“…Concerning the mosquitocidal activity, Al-Mekhlafi et alhave tested the larvicidal and ovicidal effects of the combination of M. chamomilla and Foeniculum vulgare hexane extracts against Culex pipiens. The mixture obtained showed a larvicidal activity with LC 50 of 100.3 mg/mL after 72 h exposure [28]. In addition, an ovicidal activity was reported with a decrease in egg hatchability from 95 to 15% at doses ranging from 62.5 to 500 mg/mL.…”
Section: Antiparasitic and Insecticidal Activitiesmentioning
confidence: 82%
“…Generally, M. chamomilla's effect on oxidative stress, bacterial, and fungal strains varied depending on several factors, including plant origin, organ used, extraction solvent, and technique. In addition, M. chamomilla exhibited antiparasitic, insecticidal [27,28], anti-diabetic [29], anticancer [30,31], and anti-inflammatory activities [32] (Figure 1). Based on the wide range of pharmacological activities demonstrated by M. chamomilla, its possible use in several fields has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…aegypti [20][21][22] , and Culex quinquefasciatus 23 . Furthermore, combined formulations of EOs and EO constituents showed even higher e cacy than their individual EOs [24][25] . For example, Soonwera et al 26 reported that a combined trans-anethol + I. verum EO formulation provided complete mortality against Ae.…”
Section: Introductionmentioning
confidence: 98%